Warfare in Peacetime Proxies and State Powers - Harmon, Christopher C. (Marine Corps University Press (MCUP), 2023)
Warfare in Peacetime offers an expansive and elaborated portrait of overseas proxy wars. The structure and substance will prepare observers, analysts, and participants seeking to understand challenges before American and other statesmen. The work helps frame the morass in Syria, with all its foreign links; the contest for influence in Libya, where innumerable hands vie for dominance; the fighting in Yemen, where Houthi Shia organizations backed by Iranian sponsors battle Sunni tribes; and life along the borders of Russian expansionism, where Ukrainians plea for outside assistance, including weapons from Washington. Such ongoing "warfare in peacetime" has a thousand precedents in a dozen ages, including our day, and some of the patterns are explored along with detailed case studies.